Study of technical efficiency in field schools from Nicaragua - Zuniga-Gonzalez, Carlos Alberto (2022)
The article analyzed the technical efficiency of the technological development centers (CDT) in the process of adopting new knowledge, of the technological process for the production of vegetables and basic grains, at the primary level of INTA extension workers, during the 2010 cycle- 2011. The data records for the horticultural and basic grains of the CDTs of the Centro Experimental de Occidente (CEO) Posoltega INTA Pacífico Norte, Centro de Investigación Agropecuaria (CENIA) Managua and Campos Azules (CA), Masatepe were used. The materials used were organized with the methodology of the Field Schools. The data resulting from the training were processed with the SPSS statistical package and DEAP 2.0 software to measure technical efficiency for each CDT studied. The sample was 103 CDC students in the CEO, CENIAB and CA. The methodology applied to determine the Technical Efficiency was known as the Malmquist Indices, and the analysis of enveloping data (DEA) to evaluate the Field Schools used to transfer technology to INTA extension technicians in the Pacific CDTs. The results showed that the ECAs in their first phase reached 82% of their capacity in the three CDTs studied, the CEO Posoltega reached 46% of their capacity, while the others were efficiently maintained at 100% of their technical efficiency, which implies the best conditions for phase II of the ECAs aimed at promoters and producers.